APPLICATION OF BUSINESS INTELLIGENCE TECHNIQUES TO ANALYZE IT PROJECT MANAGEMENT DATA - Zachariah, Steffi; Khadakkar, Damini; Sharma, Vinay Kumar (IJRDO -Journal of Computer Science Engineering, 2017)
In today’s world web is the need of hour. Mostof the crucial transactions and tasks are being done onlinein the form of web applications. Testing these webapplications is an important task. Testing a webapplication manually is tedious, so there is a need to gofor automation testing. In automation testing there isutilization of a product device to run repeatable testsagainst the application to be tried. There are various focalpoints of automation testing. There are various opensource and business devices accessible for testmechanization. Selenium is one of the broadly utilizedopen source device for test computerization. Testautomation enhances the effectiveness of programmingtesting procedures. Test automation gives quick criticismto engineers. It additionally discovers the imperfectionswhen one may miss in the manual testing. In testautomation we can perform boundless emphases fortesting the same example of code ceaselessly commonly.The application of this tool can be seen in the automationof monthly allowance calculation of the employees of anorganisation. Manually this tasks usually takes more thana week’s span but the use of Selenium IDE can reduce itupto a few hours.